2011
DOI: 10.1186/1471-2091-12-54
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2a (PP2A) binds within the oligomerization domain of striatin and regulates the phosphorylation and activation of the mammalian Ste20-Like kinase Mst3

Abstract: BackgroundStriatin, a putative protein phosphatase 2A (PP2A) B-type regulatory subunit, is a multi-domain scaffolding protein that has recently been linked to several diseases including cerebral cavernous malformation (CCM), which causes symptoms ranging from headaches to stroke. Striatin association with the PP2A A/C (structural subunit/catalytic subunit) heterodimer alters PP2A substrate specificity, but targets and roles of striatin-associated PP2A are not known. In addition to binding the PP2A A/C heterodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 44 publications
(71 reference statements)
6
119
2
Order By: Relevance
“…STRN4, a regulatory subunit of PP2A, directly associated with MINK1, and depletion of STRN4-induced multinucleated cells and inhibited abscission. Striatins-associated PP2A has been reported to dephosphorylate and inactivate serine/threonine kinase 24 (STK24), a member of the germinal center kinases that is known to complex with striatins (31). Similarly, we found that STRN4 could reduce the catalytic activity of MINK1 in the presence of structural and catalytic subunits of PP2A.…”
Section: Discussionmentioning
confidence: 59%
“…STRN4, a regulatory subunit of PP2A, directly associated with MINK1, and depletion of STRN4-induced multinucleated cells and inhibited abscission. Striatins-associated PP2A has been reported to dephosphorylate and inactivate serine/threonine kinase 24 (STK24), a member of the germinal center kinases that is known to complex with striatins (31). Similarly, we found that STRN4 could reduce the catalytic activity of MINK1 in the presence of structural and catalytic subunits of PP2A.…”
Section: Discussionmentioning
confidence: 59%
“…Striatins are a novel family of Bٞ type regulatory subunits that directly interact with PP2A A subunits, and indirectly interact with some GCKs using adaptor molecules (Fig. 1A) (7)(8)(9)(10)(11)(12). Because inhibition of PP2A using okadaic acid causes phosphorylation of MOB and hyperphosphorylation of striatins, PP2A may thus regulate striatins and the associated MOB proteins to modify the cytoskeleton and its interactions with membrane structures (10,11).…”
Section: Striatin-interacting Phosphatase and Kinase (Stripak)mentioning
confidence: 99%
“…GCKIII kinases, along with their interacting protein CCM3, are known to be constituents of a conserved multi-protein complex known as the striatin-interacting phosphatase and kinase (STRIPAK) complex (Goudreault et al, 2009). In addition to GCKIII kinases and CCM3, STRIPAK contains the catalytic and scaffolding subunits of protein phosphatase-2A (PP2A) along with a specific family of regulatory subunits known as striatins (STRN1, STRN3 and STRN4), as well as STR-interacting proteins STRIP1 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…and STRIP2, Mob-domain-containing protein MOB3 and the membrane-anchoring protein SLMAP (Goudreault et al, 2009;Kean et al, 2011). The STRIPAK complex has been shown to negatively regulate MST3 and MST4 kinase activities, most likely by dephosphorylating their activation segments through PP2A (Madsen et al, 2015).…”
Section: E-2mentioning
confidence: 99%